Correction: Controlled size and morphology, and phase transition of YF3:Yb3+, Er3+ and YOF:Yb3+, Er3+ nanocrystals for fine color tuning. Issue 3 (23rd December 2015) - Zhu, Yongsheng; Xu, Wen; Cui, Shaobo; Liu, Mao; Lu, Cheng; Song, Hongwei; Kim, Dong-Hwan
Abstract : Correction for 'Controlled size and morphology, and phase transition of YF3 :Yb 3+, Er 3+ and YOF:Yb 3+, Er 3+ nanocrystals for fine color tuning' by Yongsheng Zhu et al., J. Mater. Chem. C, 2016, DOI: ; Web:10.1039/c5tc03473f .